A resilient and sustainable closed-loop supply chain using multiple sourcing and information sharing strategies - Mehrjerdi, Yahia Zare; Shafiee, Mohammad (Journal of cleaner production, 2021)
The interaction of sustainability and resilience has not been sufficiently addressed in the supply chain literature. Applying sustainability and resilience concepts into a supply chain means the simultaneous optimization of the cost and recourses, including human and environmental ones, for facing possible risks. Thus, the primary motivation of this paper is to consider sustainability and resilience in a closed-loop supply chain simultaneously. For this purpose, the specialists and academics were asked to identify the impacts of supply chain’s strategies on the resilience criteria in linguistic variables. Then, the resulting matrix was solved using fuzzy TOPSIS, and the information sharing and multiple sourcing were selected as the first and second strategies. Accordingly, a new multi-objective mixed-integer programming model was formulated for a closed-loop supply chain. In this research, different dimensions of sustainability have been taken into account through reducing the total cost, energy consumption, and pollution and increasing job opportunities. Information sharing and multiple sourcing strategies have been employed in model development for making supply chain more resilient. The real data of a tire industry was used for validating the proposed model, and the model was solved using the improved version of the augmented ε-constraint (AUGMECON2) method. The results emphasized the necessity of combining sustainability and resilience in the closed-loop supply chain. •Applying sustainability and resilience simultaneously to a closed-loop supply chain.•Investigating the role of multiple sourcing and information sharing.•Ways to make a supply chain network resilient.•Solving proposed model using the improved version of the augmented ε-Constraint solution technique.•Applying the proposed model to the case of the tire industry.